A Usability and Acceptance Evaluation of the Use of Augmented Reality for Learning Atoms and Molecules Reaction by Primary School Female Students in Palestine. (December 2019) - Ewais, Ahmed; Troyer, Olga De
The chemical reaction between different molecules is an important learning subject in a chemistry course. Especially for elementary school students, this can be an abstract concept and therefore difficult to understand. One way to facilitate this learning process is to use Augmented Reality (AR) technology, which is considered as an added value compared with classical learning materials such as textbooks, two-dimensional images, video, and so forth. Among the different advantages of using AR technology in the context of the educational domain is the fact that three-dimensional technology is offering a safe environment especially if the students have to perform critical tasks such as simulating chemical reactions. This work investigates students' attitude toward the use of a mobile AR application for learning atoms' and molecules' reactions. In particular, we focused on female students because, in general, female students show less interest in science and technology than male students. We were keen to investigate whether the use of AR technology could change this attitude. The students are able to interact with different AR components to explore the possible reactions in a three-dimensional interface, to understand the structure and shape of atoms and molecules, and to view related explanations in their native language, that is, the Arabic language. The mobile AR application was evaluated by a class of 12- to 13-year-old (7th grade) students in a Palestinian primary school. The number of participants was 50, all female students. After analyzing the results, we can conclude that these female students had a positive attitude toward the use of this AR application in their learning process.